INCREASING WORK PRODUCTIVITY THROUGH ORGANIZATIONAL CULTURE, VISIONARY LEADERSHIP AND ACHIEVEMENT MOTIVATION - Billy Komara (SUJANA: Education and Learning Review, 2023)
In educational world, teachers are the conservators, transmitters, transformers and organizers that plays an important role in teaching and learning activities. Then, teacher’s commitment is important to improve the education in Indonesia, since they have a big role in conducting the teaching activities in the clasroom with the aims to produce quality students. This research aims to find optimal strategies, ways, and solutions to increase organizational commitment by examining the influence of transformational leadership, motivation, trust and job satisfaction on organizational commitment. The research method used in this research is a survey method with a correlational approach and Path analysis. Based on research result, Organizational commitment can be improved by strengthening transformational leadership, motivation, trust and job satisfaction, along with improving weak indicators and maintaining good indicators of examined variables. Through SITOREM analysis, the optimal solution for increasing organizational commitment can be found. Based on these results, the teachers' organizational commitment can be increased by strengthening transformational leadership, trust, job satisfaction, and motivation variables.